Science Teachers’ Teaching Styles, Students’ Learning Styles and Their Academic Performance in The Secondary Public Schools of Zambales - Ariem, Jennifer Garingarao; Cabal, Esmen Macadaan (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This research was conducted to determine the relationship of Science teachers’ teaching styles and the students’ learning styles and academic performance. The study was conducted among the public secondary school in Subic, Zambales during the academic year 2018 – 2019. The descriptive survey research design was used where the teaching styles of eighty-five teachers and six hundred high school students. Data were analyzed using the percentage, mean and chi square test. The findings of the study revealed that the science teachers are adults with the most of them are female. The students are teenagers mostly male in Grade 8. The teaching styles of the science teachers is of a formal authority and the learning styles of the students is generally visual. The academic performance in science is satisfactory. The teaching styles of the teachers was dependent on education, field of specialization, length of service. The learning styles of the students were not dependent significantly on their age and year level. The learning styles of the students were significantly dependent on teaching styles of their science teachers and the academic performance of the students significantly dependent on the teaching styles of the science teachers. The academic performance of students are significantly dependent on their learning styles. With these findings and conclusions follow up studies exploring other factors affecting the performance level of the students in Science is recommended as well as the effectiveness of the various teaching styles and learning styles to promote learning and better understanding in the subject must be conducted.